Teaching with audiovisual and digital resources: an innovative experience in posgraduate education in Peru - P.P. Ames Ramello (Universitat Politècnica de València, 2019)
This paper presents an innovation that took place in the Pontifical Catholic University of Peru in the academic year 2016. The innovation use TIC in three ways: 1) incorporating audiovisual materials in all lessons of a course, in a way that motivate the discussion and analysis of educational issues from the point of view of social sciences and in dialogue with reading material; 2) promoting the use of PAIDEIA (a Moodle) for the work and evaluation of the course, and for managing the audiovisual, digital and bibliographic resources; 3) offering the option to present their final assignment in an audiovisual format. Methods for evaluation were mixed, using both quantitative and qualitative methods, such as surveys and focus group. Results show a positive impact of audiovisual material in combination with bibliographic resources and oral presentations, fostering a greater participation and reflection among students, and a greater consciousness of their own learning. Students valued positively the use of PAIDEIA (Moodle platform), unknown for most students, and they learn to use it. Students also produced audiovisual material that reflected their learning. Such materials were in turn used for other course as audiovisual support material.